2013
DOI: 10.1371/journal.pone.0064377
|View full text |Cite|
|
Sign up to set email alerts
|

Cell- and Tissue-Specific Transcriptome Analyses of Medicago truncatula Root Nodules

Abstract: Legumes have the unique ability to host nitrogen-fixing Rhizobium bacteria as symbiosomes inside root nodule cells. To get insight into this key process, which forms the heart of the endosymbiosis, we isolated specific cells/tissues at different stages of symbiosome formation from nodules of the model legume Medicago truncatula using laser-capture microdissection. Next, we determined their associated expression profiles using Affymetrix Medicago GeneChips. Cells were collected from the nodule infection zone di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 99 publications
7
80
0
4
Order By: Relevance
“…Nevertheless, comparison of the expression patterns indicates that AtPLT3 and Medtr5g031880 are expressed in the RM, whereas AtPLT7 and Medtr8g068510 are not [Galinha et al, 2007;Prasad et al, 2011; The Medicago truncatula Gene Expression Atlas Project (http:// mtgea.noble.org/v3/)]. Based on these data and to keep in line with the previously designated MtPLT2 (Limpens et al, 2013), we utilize from now on the following nomenclature: Medtr2g098180 (MtPLT1), Medtr4g065370 (MtPLT2), Medtr5g031880 (MtPLT3) and Medtr7g080460 (MtPLT4) ( Table 1). The proposed gene annotations were subsequently used to design primers (supplementary material Table S5) to enable gene expression studies by qPCR.…”
Section: Medicago Truncatula Orthologs Of Atplt Genesmentioning
confidence: 93%
See 4 more Smart Citations
“…Nevertheless, comparison of the expression patterns indicates that AtPLT3 and Medtr5g031880 are expressed in the RM, whereas AtPLT7 and Medtr8g068510 are not [Galinha et al, 2007;Prasad et al, 2011; The Medicago truncatula Gene Expression Atlas Project (http:// mtgea.noble.org/v3/)]. Based on these data and to keep in line with the previously designated MtPLT2 (Limpens et al, 2013), we utilize from now on the following nomenclature: Medtr2g098180 (MtPLT1), Medtr4g065370 (MtPLT2), Medtr5g031880 (MtPLT3) and Medtr7g080460 (MtPLT4) ( Table 1). The proposed gene annotations were subsequently used to design primers (supplementary material Table S5) to enable gene expression studies by qPCR.…”
Section: Medicago Truncatula Orthologs Of Atplt Genesmentioning
confidence: 93%
“…Recent studies showed that orthologs of AtPLT genes, named MtPLT2(Medtr4g65370) and MtBBM/PLT4(Medtr7g080460) are expressed in the NM (Boutilier et al, 2002;Hofhuis et al, 2013;Limpens et al, 2013;Roux et al, 2014). We asked whether the other Medicago PLT orthologs are also expressed in the NM and performed reciprocal BLAST searches (in Mt4.0v1) using the AtPLT protein sequences as a query to identify their homologs in Medicago (Table 1; supplementary material Fig.…”
Section: Medicago Truncatula Orthologs Of Atplt Genesmentioning
confidence: 99%
See 3 more Smart Citations